ADRB2 inhibition suppresses cancer immune evasion by regulating tumor SOX10-PD-L1 axis and T cell function - Yang Wang; Wei Zhang; Yu Zhang; Ling Chen; Shiyu Wang; Kun Song; Feng Yu; Jing Ouyang; Shan Cao; Cong Peng; Dongbo Liu; Yingying Dai; et al. (Journal for ImmunoTherapy of Cancer)
Background Chronic stress is known to promote cancer progression, in part by modulating immune responses through the β2-adrenergic receptor (ADRB2). Inhibiting ADRB2 with β-blockers has demonstrated potential in boosting the effectiveness of immune checkpoint inhibitors across a spectrum of cancers, yet the precise mechanisms remain to be fully elucidated.Methods In vivo and in vitro experiments were performed to evaluate the role of ADRB2 in melanoma models, including its effects on T cells. RNA sequencing analysis highlighted the importance of the transcription factor SRY-related HMG-box 10 (SOX10), which transcriptionally regulates programmed death-ligand 1 (PD-L1). This regulatory role was further validated using luciferase reporter assays and chromatin immunoprecipitation-PCR assays. Mechanistic studies focused on ADRB2 signaling through protein kinase A (PKA) and its downstream target SOX10. To investigate SOX10’s role in mediating the effects of ADRB2, knockdown and overexpression experiments were conducted. Additionally, similar studies in colorectal cancer (CRC) models confirmed the conserved function of the ADRB2-SOX10-PD-L1 axis.Results This study explores the role of ADRB2 in regulating tumor PD-L1 expression and T cell functionality, offering insights for cancer immunotherapy. Clinical data revealed that patients with melanoma with high ADRB2 expression responded better to programmed cell death protein 1 inhibitors. In melanoma models, ADRB2 inhibition reduced PD-L1 expression, enhanced T cell infiltration, and promoted antitumor immunity, while ADRB2 activation had the opposite effect. Mechanistically, ADRB2 signaling through PKA upregulated SOX10, which transcriptionally modulates PD-L1. SOX10 knockdown replicated the effects of ADRB2 inhibition, while SOX10 overexpression reversed them. Similar findings in CRC models confirmed the conserved role of the ADRB2-SOX10-PD-L1 axis. Targeting ADRB2 and SOX10 may enhance immune checkpoint inhibitor efficacy in cancer treatment.Conclusions These findings underscore the potential of ADRB2 and SOX10 as therapeutic targets for mitigating stress-induced immunosuppression and for augmenting the effectiveness of immunotherapies in a variety of cancer types.